Partial purification and biochemical characterization of an alkaline esterase from Sorghum bicolor - Fabiana Guillen Moreira Gasparin; Marcio de Barros; Gabriela Alves Macedo (Acta Scientiarum. Biological Sciences, 2020)
Esterases are enzymes that present good potential for industrial applications since they catalyze the formation or cleavage of ester bonds in water-soluble substrates, and sorghum seeds can represent an alternative source of this enzyme. The extraction of esterase from sorghum seeds is an economical alternative to obtain an enzyme of great interest. Esterases may improve the quality or accelerate the maturation of cheeses, cured bacon and fermented sausages and may also resolve racemic mixtures. Recently, seed esterases have been the focus of much attention as biocatalysts. In some cases, these enzymes present advantages over animal and microbial lipases due to some quite interesting features such as specificity and low cost, being a great alternative for their commercial exploitation as industrial enzymes The esterase studied here was extracted from sorghum seeds and some of its biochemical properties determined using synthetic substrates (p-nitrophenyl butyrate, caprylate, laurate and palmitate). The enzyme presented optimum activity at pH 8.0 and was stable in all the pH ranges studied. The optimum temperature for its activity was 40ºC but it showed low stability at this temperature (40% relative activity). The values derived for Km and Vmax were 0.67mM and 125 U.mg-1, respectively, obtained using p-nitrophenyl butyrate as the substrate. The enzyme showed an increase in activity when K2HPO4 was added to the reaction medium, but the ions Mn2+, CO+, Hg+ and Fe2+ strongly inhibited the enzyme activity. This enzyme showed a preference for the hydrolysis of short chain fatty acids. The characteristics of sorghum esterase are very similar to those of the microbial esterases used in detergent processing.